Effects of Reciprocal Ia Inhibition on Contraction Intensity of Co-contraction - Hirabayashi, Ryo; Edama, Mutsuaki; Kojima, Sho; Nakamura, Masatoshi; Ito, Wataru; Nakamura, Emi; Kikumoto, Takanori; Onishi, Hideaki (Frontiers in Human Neuroscience, 2019)
Introduction: Excessive co-contraction interferes with smooth joint movement. One mechanism is the failure of reciprocal inhibition against antagonists during joint movement. Reciprocal inhibition has been investigated using joint torque as an index of intensity during co-contraction. However, contraction intensity as an index of co-contraction intensity has not been investigated. In this study, we aimed to evaluate the influence of changes in contraction intensity during co-contraction on reciprocal inhibition. Methods: We established eight stimulus conditions in 20 healthy adult males to investigate the influence of changes in contraction intensity during co-contraction on reciprocal inhibition. These stimulus conditions comprised a conditioning stimulus-test stimulation interval (C-T interval) of −2, 0, 1, 2, 3, 4, or 5 ms plus a test stimulus without a conditioning stimulus (single). Co-contraction of the tibialis anterior and soleus muscles at the same contraction intensity was examined at rest and at 5%, 15%, and 30% maximal voluntary contraction (MVC). Results: At 5% and 15% MVC in the co-contraction task, the H-reflex amplitude was significantly decreased compared with single stimulation at a 2-ms C-T interval. At 30% MVC, there was no significant difference compared with single stimulation at a 2-ms C-T interval. At a 5-ms C-T interval, the H-reflex amplitude at 30% MVC was significantly reduced compared with that at rest. Discussion: The findings indicated that during co-contraction, reciprocal Ia inhibition worked at 5% and 15% MVC. Contrary inhibition of reciprocal Ia inhibition did not apparently work at 30% MVC, and presynaptic inhibition (D1 inhibition) might work.